An Overview of Dangers of Drug Abuse to a Muslim Man and Relations - Sharu, Aliyu Umar (Darul Yasin Al Sys, 2024)
The aim of this research paper is to deliberate on the dangers of drug abuse to Muslim (and other humans). Drug abuser is a threat to humans that has been inflicting humans from ancient time to date. Drug abuse kill, maim, harm, and destroy abusers and related members of the society. A conceptual review made in this work deliberate on the following items of drug abuse among others: Islamic concepts of drug abuse, drug abuse in the context of health, drivers of drug abuse, dangers of drug abuse, examples of drugs of abuse and their respective effects, etc. It is important to re-alert the society (especially policy makers and stakeholders) to take heed and stringent measures to prevent drug abuse through disparate means including utilization of religious interventions.